Distance education and dropout in higher education in the Amazon context: a literature review study (Research, Society and Development, 2020)
Distance Education (EaD) consolidates itself as the alternative to democratize access to higher education in Brazil and specifically in the northern region, this path has been a reference for educational continuation, but with the adversities of evasion. Given this, we aim in this literature review to describe the probable causes for the evasion of students in distance education in higher education in the Amazon context, factors that can interfere with access, permanence and learning of students. As methodological procedures, we opted for bibliographic research with a qualitative approach, using databases such as Scielo and Google Scholar between the years 2010 to 2019. The results revealed several probable causes that lead EaD students to evade, among the most present are connected social, economic and institutional issues. We consider that, according to our findings and due to the growth of distance education, the difficulties of studying at a distance are undeniable, however, institutions and their teaching-learning spaces need to use resources and instruments that motivate and assist students in their specificities. in the Amazon context.